2006
DOI: 10.1159/000096006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on Scolicidal Efficacy of Propolis

Abstract: Background: Propolis is a resinous material collected by bees from various plants. It has antimicrobial, antioxidative, immunostimulative, and regenerative properties. We determined the scolicidal effect of propolis in different concentrations and various exposure times. Materials and Methods: Tubes containing Echinococcus granulosus protoscoleces were supplementedwith different concentrations of ethyl alcohol extract of propolis. At the end of the incubation times, viabilityof protoscoleces was assessed by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Kismet and Kilicoglu et al determined that 1 µg/ml concentration of propolis [16] (a resinous material collected by bees from various plants) and 10% honey concentrations [17] killed all of the protoscolices at the end of 3 min. In the in vivo part of the study, intraperitoneal application of propolis and honey did not cause any side effects or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Kismet and Kilicoglu et al determined that 1 µg/ml concentration of propolis [16] (a resinous material collected by bees from various plants) and 10% honey concentrations [17] killed all of the protoscolices at the end of 3 min. In the in vivo part of the study, intraperitoneal application of propolis and honey did not cause any side effects or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the antibacterial effect of honey on ocular flora has been displayed [18] . Furthermore, the scolicidal efficacy of propolis, which is a resinous material obtained by honey bees from plants or flowers, has been shown in cystic hydatid disease [19] . Recently, it has been found that honey leads to increased levels of NO in biological fluids and to reduced liver enzymes, such as AST and ALT, in blood [20] .…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that propolis might be used as a potent scolicidal agent if it would not cause caustic sclerosing cholangitis when injected into the biliary tree. 7 We also designed another study that would compare propolis with other scolicidal agents for the side effects on liver and biliary tree.…”
Section: Discussionmentioning
confidence: 99%
“…6 In a previous study, we found that propolis was totally effective on protoscolices in low concentrations and short exposure time. 7 This study was conducted to investigate the effects of propolis on the liver and biliary tree by direct injection of propolis into the common bile ducts of the rats.…”
Section: Introductionmentioning
confidence: 99%